The Effectiveness of the Mobile Service Program by the Population and Civil Registry Office of Bolaang Mongondow Utara Regency - Festiana Lasena; Lisda Van Gobel; Agus Pariono (Formosa Journal of Applied Sciences, 2022)
This type of research is qualitative research, that Aims to determine the effectiveness of the Mobile Service Program at the Department of Population and Civil Registration of North Bolaang Mongondow Regency. This type of research is descriptive, data collection techniques use instruments in the form of observations, interviews, and literature studies. The results of this study indicate that the service time for the mobile program is according to a set schedule and is very effective, but not optimal, in terms of the distance from the population service place from the Population and Civil Registry Office to other villages, so it is very far so it is difficult to pass because the road damaged and very far away in remote areas, the supporting infrastructure for mobile service program activities is still limited and sufficient, and the number of employees who go to the field in villages is still a lack of employees who provide population management services resulting in long queues and slowing down the service process It is recommended to pay attention to service time, distance and place of service, facilities and infrastructure, and number of employees so that the implementation of the mobile service program can be maximized.